PENJUALAN BANCASSURANCE: ANALISIS SWOT DAN SEBUAH MODEL MARKETING PLAN - Iman Sidik Nusannas; Indra Maulana (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2019)
A selling cooperation between bank and insurance company, recently become a most common business model. The collaboration to sell insurance in bank branches to gain a win-win solution situation. The bank achieve fee based income from the sell of insurance product. The insurance company gain the sell performance. However the business is not always run well, the problem appears in selling insurance product at the bank branches. This research is to find the way to im/prove selling insurance product at the bank by using SWOT analysis and provide marketing plan to achieve the goal